Exploring the Impact of Internal Branding on Employee Brand Citizenship Behavior - Adamu, Lawi; Abd Ghani, Noor Hasmini; Abdul Rahman, Maria (2017)
The purpose of this study is to explore the relationship among internal branding practices and employee BCB.A self-administered questionnaire was used in obtaining data from employees of telecommunication industry.The hypotheses in the study were simultaneously tested on a sample of 254 employees out of 377 distributed, giving the response rate of 68%. SmartPls was used to assess the relationship between the variables under investigation.The findings in the study revealed positive significant relationship between brand training and employee BCB.On the other hand insignificant relationship was found between brand communication and employee BCB.Management implications and direction for future study were provided.